Peran Keterampilan Menjelaskan Guru Al-Qur’an dan Hadis dalam Pembelajaran Aktif Siswa Kelas VII MTs Insan Cendekia - Safitri, Eva; Anshari, Ahmad; Laila, Laila; Pariati, Ema; Faelasup, Faelasup (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research focuses on the role of Qur'an and Hadith teachers' explanatory skills, the application of active student learning, and its implications. A qualitative approach with field research was conducted through observations, interviews, and document analysis in grade VII of MTs Insan Cendekia. The results show that the explanatory skills of Qur'an and Hadith teachers enhance student engagement and understanding in religious education. The application of active learning methods, such as group discussions, simulations, and the use of technology, makes students more engaged and better understand the material. This active learning increases student participation, deep understanding, motivation, and social skills, thereby improving the effectiveness of Islamic religious education.